Transmission of Foot-and-Mouth Disease SAT2 Viruses at the Wildlife–Livestock Interface of Two Major Transfrontier Conservation Areas in Southern Africa - Brito, Barbara P.; Jori, Ferran; Dwarka, Rahana; Maree, Francois F.; Heath, Livio; Perez, Andres M. (Frontiers in Microbiology, 2016)
Over a decade ago, foot-and-mouth disease (FMD) re-emerged in Southern Africa specifically, in beef exporting countries that had successfully maintained disease-free areas in the past. FMD virus (FMDV) serotype SAT2 has been responsible for a majority of these outbreaks. Epidemiological studies have revealed the importance of the African buffalo as the major wildlife FMD reservoir in the region. We used phylogeographic analysis to study dynamics of FMD transmission between buffalo and domestic cattle at the interface of the major wildlife protected areas in the region currently encompassing two largest Transfrontier conservation areas (TFCA): Kavango-Zambezi (KAZA) and Great Limpopo (GL). Results of this study showed restricted local occurrence of each FMD virus SAT2 topotypes I, II and III, with occasional virus migration from KAZA to GLTP. Origins of outbreaks in livestock are frequently attributed to wild buffalo as the origin, but our results suggest that transmission from cattle to buffalo also occurs. This study contributes to understand the major dynamics of transmission and genetic variation of FMD virus SAT2 in southern Africa, which will ultimately support designing efficient strategies for the control of FMD at a local and regional level.